PROTEIN RESIDUE ANALYSIS AND AMS RADIOCARBON DATING FOR SITES 118X77, 532X, NAHANNI NATIONAL PARK RESERVE, NORTHWEST TERRITORIES - Cummings, Linda Scott (2020)
Gahnihthah Mie (Site 118X77/5342X) appears to be a single component precontact site located on the upper bank of Rabbitkettle Lake in the Northwest Territories. Charcoal recovered from two hearths was submitted for AMS radiocarbon dating to establish the period of use. In addition, four lithic tools were submitted for protein residue analysis to identify economic activity.